Digital Human Twins in the Age of Hyper-Personalisation and Ethical Complexity - Manotar Tampubolon (SEAN Institute, 2026)
The rapid rise of Digital Human Twins (DHTs) , essentially virtual replicas of real people that are constantly updated with real-time data, has opened up exciting possibilities while also raising significant ethical questions. Initially rooted in healthcare and precision medicine, the concept of digital twins has now branched out into areas like fitness, fashion, education, and emotional AI, all thanks to advancements in IoT, machine learning, and biometric technologies. This study dives into the intricate relationship between hyper-personalization and ethical considerations, looking at how digital human twins are transforming our sense of identity, autonomy, and social interactions. This research takes a narrative literature review approach, pulling together secondary data from peer-reviewed journals, industry reports, and ethical frameworks. The goal is to critically examine the interdisciplinary challenges that pop up at the crossroads of artificial intelligence, data science, psychology, healthcare, and law. This paper tackles important ethical issues like data privacy, surveillance, emotional manipulation, and informed consent. At the same time, it dives into the complex technology needed to maintain these real-time digital representations. Even though digital human twins are becoming more integrated into our daily lives, they are still not fully understood, particularly regarding their long-term effects on society. The existing academic literature lacks a unified, transdisciplinary framework that critically explores the intersection of emotional AI, biometric data, and digital identity. This paper aims to contribute to the academic conversation by addressing this gap, providing a comprehensive ethical-technological analysis, and emphasizing the urgent need for governance frameworks that prioritize human dignity and rights. As digital companions continue to evolve, this research lays a crucial groundwork for future studies and policymaking that seeks to balance innovation with ethical responsibility.